TGF-β-Containing Small Extracellular Vesicles From PM2.5-Activated Macrophages Induces Cardiotoxicity - Hu, Xiaoqi; Chen, Mo; Cao, Xue; Yuan, Xinyi; Zhang, Fang; Ding, Wenjun (Frontiers in Cardiovascular Medicine, 2022)
Numerous epidemiological and experimental studies have demonstrated that the exposure of fine particulate matter (aerodynamic diameter less than 2.5 μm, PM2.5) is closely associated with cardiovascular morbidity and mortality. Our previous studies revealed that PM2.5 exposure induced cardiac dysfunction and fibrosis. However, the corresponding underlying mechanism remains largely unaddressed. Here, PM2.5-induced cardiotoxicity are reported to be able to directly promote collagen deposition in cardiomyocytes through transforming growth factor-β (TGF-β)-containing small extracellular vesicles (sEV). The sEV transition may play important role in PM2.5-induced cardiac fibrosis. Firstly, long-term PM2.5 exposure can directly induce cardiac fibrosis and the level of sEV from serum. Secondly, PM2.5 can directly activate macrophages and increase the release of tumor necrosis factor α (TNF-α), interleukin-6 (IL-6) and TGF-β1-containing sEV. Thirdly, TGF-β-containing sEV increases the expression of α-smooth muscle actin (α-SMA), collagen I and collagen III in mouse cardiac muscle HL-1 cells. Finally, TGF-β-containing sEV released from PM2.5-treated macrophages can induce the collagen increase through the activation of TGF-β-Smad2/3 signaling pathway in HL-1 cells, from which some fibroblasts involved in cardiac fibrosis are thought to originate. These findings suggest that TGF-β-containing sEV from PM2.5-activated macrophages plays a critical role in the process of the increases in cardiac collagen content via activating TGF-β-Smad2/3 signaling pathway.